Volcano-tectonic interactions revealed by inversion of focal mechanisms: stress field insight around and beneath the Vatnajökull ice cap in Iceland - Plateaux, Romain; Béthoux, Nicole; Bergerat, Françoise; Mercier de Lépinay, Bernard (Frontiers in Earth Science, 2014)
Volcano-tectonic processes in the central part of Iceland, covered by the Vatnajökull glacier, are investigated by inversion of focal mechanisms. Working on a large catalogue of focal mechanisms determined by the Icelandic Meteorological Office, we used a damped regional-scale stress inversion method to obtain an insight of kilometric variations of the stress field. To evaluate the resolution and the stability of this stress field solution, we computed checkerboard tests, stress field models and error propagation tests. Stress field models showed a continuous stress regime between normal and strike-slip faulting, associated with a high stress shape ratio (i.e.; σ1 ≈ σ2). Two main directions of σhmin were evidenced: the first one was in agreement with the regional spreading direction of Iceland and the second one was deviated, being almost perpendicular to the first one. The deviated stress direction is sustained through the 20 year time-span of the study around the Bárðarbunga and Grimsvötn central volcanoes while the spreading direction remains predominant around the Hamarinn volcano. This result supports the hypothesis that this volcano lacks collapse caldera and shares a fissure swarm with the larger Bárðarbunga volcano. On a smaller temporal scale, during the 1996 volcanic crisis, a bimodal distribution of σhmin showed two opposite strike-slip regimes where the deviated direction dominated. Because these two states of stress T1 and T2 show stress regimes away from the Andersonian positions, P, B and T axes, the rapid flip between these two regimes may be associated with the progressive melt intrusion of a dyke.